Estudio de casos de aplicación de la justicia canónica y vulneración a los Derechos Humanos sucedidos entre 2018 y 2023. - Montenegro Tapia, Miguel Ángel (2025)
The Church has been classified as an institution responsible for protecting people's rights, based on human dignity and the common good; however, it has committed many atrocious acts professing the equality and well-being of its faithful. The general objective is to determine whether ecclesiastical courts violated Human Rights when applying the law of canonical justice. The methodology has a qualitative approach, scientific and descriptive analysis. 4 cases were considered worldwide in which ecclesiastical courts had to intervene and where Human Rights were violated, during the process or through the decision made. A checklist was used to describe each case, obtaining data through bibliographic review and analysis of resolutions and sentences taken within ecclesiastical courts. The outstanding results of this research consist of demonstrating the actions of ecclesiastical courts, the right to personal integrity, justice, protection, freedom of expression, dignity, marriage, sexual integrity, and their correspondence to Human Rights.